Does mindfulness matter for creativity? Relationships with well-being and creative self-efficacy - Junça Silva, A.; Mendonça, H.; Ferreira, M. C. (18th Congress of the European Association of Work and Organizational Psychology, 2017)
Purpose Studies have suggested that mindfulness is associated with increased health, well-being, and creativity. However, there is a lack of research about the impacts of mindfulness on employees. Mindfulness is defined as a psychological state in which employees pay attention to the present moment while working. This study aims to broaden the understanding of mindfulness in work context, specifically the influence of mindfulness on creativity. This influence can be direct and indirect, when it is shaped by well-being and creative self-efficacy. Design/Methodology A cross-sectional study was carried out using a sample of 176 full time Brazilian workers from public or private sector. Data analysis was done using PROCESS for SPSS. Findings The research findings support that mindfulness positively predicts creativity. Additionally, findings suggest that the relationship between mindfulness and creativity is better explained through well-being and creative self-efficacy. The double mediation model was confirmed. Limitations The cross-sectional nature of the study limits the generalization of its results. Also, self-reported data is subjected to common method biases. Research/Practical Implications The study fills a gap in the literature about creativity and justifies the development of trainings focused on mindfulness at work. Originality/Value The research highlights the understanding of emerging literature on mindfulness at work by establishing personal conditions that promote or inhibit health at work, which in turn enhances creativity and also contributes to building up the knowledge about Positive Organizational Psychology. The study makes theoretical and practical contributions by describing other mechanisms that stimulate work creativity.